Post-Quantum Algorithms on ARM Trusted Execution Environment (TEE): findings of this industrial challenge - Andrade, Ewerton; Goes, Cristiano Coimbra; Sousa, Janislley Oliveira de (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2024)
The emergence of polynomial time algorithms for factoring large integers and computing discrete logarithms, alongside the rise of quantum computing, poses significant challenges to secure computing. Numerous endeavors have been undertaken to address this issue, particularly by governmental agencies and academic institutions. Nevertheless, only a handful of commercial solutions currently integrate Post-Quantum Cryptography (PQC) algorithms. The integration of such algorithms is even more limited in Advanced RISC Machines (ARM) Trusted Execution Environment (TEE). In light of this, we conducted a study using OP-TEE emulated on QEMU to explore the challenges and opportunities of embedding Key Encapsulation Mechanisms (KEMs) in ARM TEE. Through our experiments and collected data, it was verified that the overhead introduced by TEE communication is negligible. Furthermore, our study shows that certain PQC algorithms offer better processing times and security than current solutions.